Professional degradation: social psychological aspects - Кульчицька, Анна Валеріївна; Kulchytska, Anna V. (Cхідноєвропейський національний університет імені Лесі Українки, 2014)
Effective opposition to psychological and emotional stress foresees conscious activity of every worker regarding his health. Health can’t be purchased, it is the main capital of a man and of an organization that he works in. Indisputably, a labour protection needs complex of organizational, ergonomic, psychoprophylactic measures and responsibility from the side of employer and state.
Keywords: professional destruction; reaction of alarm; stage of firmness; stage of exhaustion; emotional exhaustion; depersonalization; stress